2019
DOI: 10.1108/hff-11-2018-0619
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of flow with large eddy simulation at Re = 3900

Abstract: Purpose Over the past few decades, the flow around circular cylinders has been one of the highly researched topics in the field of offshore engineering and fluid-structure interaction (FSI). In the current study, numerical simulations for flow around a fixed circular cylinder are performed at Reynolds number (Re) = 3900 with the LES method using the ICEM-CFD and ANSYS Fluent tool for meshing and analysis, respectively. Previously, similar studies have been conducted at the same Reynolds number, but there have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…The number of bubbles in the wake is huge and their diameters are different. Among them, large bubbles will rise quickly, break, and disappear, while small bubbles can survive in seawater for more than ten minutes or even dozens of minutes [2]. Due to the obvious difference of bubble density, compressibility, and other parameters from seawater and the influence of turbulence in the wake, the bubble distribution in the wake is uneven, which leads to the obvious difference between the transmis-sion characteristics of sound wave and light wave in the wake and that in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…The number of bubbles in the wake is huge and their diameters are different. Among them, large bubbles will rise quickly, break, and disappear, while small bubbles can survive in seawater for more than ten minutes or even dozens of minutes [2]. Due to the obvious difference of bubble density, compressibility, and other parameters from seawater and the influence of turbulence in the wake, the bubble distribution in the wake is uneven, which leads to the obvious difference between the transmis-sion characteristics of sound wave and light wave in the wake and that in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…In all these case studies, number of elements on cylinder circumference (N c ) × number of elements on cylinder in radial direction (N R ) are 240×60 respectively. 240x60 is taken from the study of Khan et al [7], who concluded that reduction in number of circumferential and radial nodes will overestimate the value of C d , reduction in recirculation length, and a delay in flow separation.…”
Section: Resultsmentioning
confidence: 99%
“…The flow around a fixed cylinder at Re = 3900 come under the lower subcritical flow regime, which is highly sensitive in terms of flow separation, boundary layer nature, recirculation length, wake characteristics, and other hydrodynamic coefficients [3]. The availability of large-scale experimental and numerical data [4][5][6][7][8][9][10] for the flow around cylinders at Re = 3900 makes it an excellent benchmark case for assessing the capability of computational tools and process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MHD flow and heat transfer characteristics past a permeable stretching sheet have been studied analytically by Hayat et al (2011). Enormous research works (Ullaha et al, 2017;Sheikh and Abbas, 2015;Hayat et al, 2017a;AnkiReddy and Das, 2016;Hayat et al, 2017b;Turkyilmazoglu, 2018aTurkyilmazoglu, , 2018bKhan et al, 2019aKhan et al, , 2019bKhan et al, , 2019cKhan et al, , 2019dHayat et al, 2016;Turkyilmazoglu, 2017) have been done on the MHD flow of heat and mass transfer over a stretching surface under different physical situations.…”
Section: Introductionmentioning
confidence: 99%